Molecular mechanisms and therapeutic targets in pediatric brain tumors - Liu, Kun-Wei; Pajtler, Kristian Wilfried; Jones, Barbara Christine; Pfister, Stefan (Science signaling, 2017)
Brain tumors are the leading cause of cancer-related deaths in children, and therapies are few and cause devastating long-term side effects. Genomics and epigenomics have revealed that these tumors are molecularly diverse and appear to be driven by mutations in various signaling pathways, which may present new opportunities for a more targeted therapeutic intervention. In this Review, which contains three figures and 224 references, we discuss our current understanding of the molecular basis of the three most common malignant pediatric brain tumors (medulloblastoma, ependymoma, and high-grade glioma) and the prospects for developing safer and more effective therapies.
Gesehen am 16.10.2018